PENERAPAN MODEL PEMBELAJARAN INQUIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN DASAR AKUNTANSI DI SMKN 4 KOTA SERANG - Nely Hartika; Ira Ismeylia Saputri (FKIP, Universitas Banten Jaya, 2019)
This study aims to find out how the application of inquiry learning models in accounting subjects in class X AK in SMKN 4 Serang City and to find out whether the inquiry learning model can improve student learning outcomes in class X AK in Accounting Basic Subjects in SMK 4 Serang City.This research uses a class action research method which consists of two cycles. Each cycle consists of four stages, namely planning, implementing, observing reflection. The subjects of this study were participants in grade X SMK 4 Serang City consisting of 36 students and teachers in Accounting as a team of collaborators. These results indicate that the Inquiry learning model can improve student learning outcomes based on cycle one, from 36 students who succeeded in getting grades above the KKM of 36.56% with an average value of 66, whereas in the second cycle there was a significant increase to be 100% with an average value of 82.